Amino acids stimulate cholecystokinin release through the Ca(2+)-sensing receptor - Wang, Yu (American Physiological Society, 2011)
Cholecystokinin (CCK) is produced by discrete endocrine cells in the proximal small intestine and is released following the ingestion of food. CCK is the primary hormone responsible for gallbladder contraction and has potent effects on pancreatic secretion, gastric emptying, and satiety. In addition to fats, digested proteins and aromatic amino acids are major stimulants of CCK release. However, the cellular mechanism by which amino acids affect CCK secretion is unknown. The Ca(2+)-sensing receptor (CaSR) that was originally identified on parathyroid cells is not only sensitive to extracellular Ca(2+) but is activated by extracellular aromatic amino acids. It has been postulated that this receptor may be involved in gastrointestinal hormone secretion. Using transgenic mice expressing a CCK promoter driven/enhanced green fluorescent protein (GFP) transgene, we have been able to identify and purify viable intestinal CCK cells. Intestinal mucosal CCK cells were enriched >200-fold by fluorescence-activated cell sorting. These cells were then used for real-time PCR identification of CaSR. Immunohistochemical staining with an antibody specific for CaSR confirmed colocalization of CaSR to CCK cells. In isolated CCK cells loaded with a Ca(2+)-sensitive dye, the amino acids phenylalanine and tryptophan, but not nonaromatic amino acids, caused an increase in intracellular Ca(2+) ([Ca(2+)](i)). The increase in [Ca(2+)](i) was blocked by the CaSR inhibitor Calhex 231. Phenylalanine and tryptophan stimulated CCK release from intestinal CCK cells, and this stimulation was also blocked by CaSR inhibition. Electrophysiological recordings from isolated CCK-GFP cells revealed these cells to possess a predominant outwardly rectifying potassium current. Administration of phenylalanine inhibited basal K(+) channel activity and caused CCK cell depolarization, consistent with changes necessary for hormone secretion. These findings indicate that amino acids have a direct effect on CCK cells to stimulate CCK release by activating CaSR and suggest that CaSR is the physiological mechanism through which amino acids regulate CCK secretion.